Clinical and Biological Characteristics of Severe Malaria in Children under 5 Years Old in Benin - Xiao Ma; Xin Fan; Kora Chabi Youssaou; Junfei Zhang; Xingyi Wang; Guoqiang Zheng; Shuping Tian; Yujing Gao (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Malaria is a global public health concern, mainly occurring in sub-Saharan Africa. Children infected with malaria are more likely to develop severe disease, which can be fatal. During COVID-19 in 2020, diagnosing and treating malaria became difficult. We analyzed the clinical characteristics and laboratory indicators of children with severe malaria in Benin to provide important information for designing effective prevention and treatment strategies to manage pediatric cases. Methods. Clinical characteristics of pediatric patients with severe malaria admitted to two hospitals in Benin (Central Hospital of Lokossa and Regional Hospital of Natitingou, located ∼650 kilometers apart) were collected from January to December 2020. Patients were grouped according to age (group A: 4–12 months old, group B: 13–36 months old, and group C: 37–60 months old), and clinical and laboratory indicators were compared. The incidences of severe pediatric malaria in both hospitals in 2020 were calculated. Inclusion, exclusion, and blood transfusion criteria were identified. Results. We analyzed 236 pediatric cases. The main clinical symptoms among all patients were severe anemia, vomiting, prostration, poor appetite, dysphoria, and dyspnea. Over 50% of patients in group A experienced vomiting and severe anemia. Most patients in group B had severe anemia and prostration. Delirium affected significantly more patients in group C than in groups A and B. In group C, the hemoglobin and hematocrit levels were significantly higher p<0.05, and the leukocyte count was significantly lower p<0.01 than in groups A and B. Parasitemia was significantly higher in group C than in group A p<0.01. Twelve deaths occurred. Conclusions. Severe pediatric malaria is seasonal in Benin. The situation in children under 5 years old is poor. The main problems are severe disease conditions and high fatality rates. Effective approaches such as prevention and early and appropriate treatment are necessary to reduce the malaria burden in pediatric patients.